let IT1, IT2 be Point of (); :: thesis: ( IT1 in P /\ Q & ( for g being Function of I,(() | P)
for s2 being Real st g is being_homeomorphism & g . 0 = p1 & g . 1 = p2 & g . s2 = IT1 & 0 <= s2 & s2 <= 1 holds
for t being Real st 0 <= t & t < s2 holds
not g . t in Q ) & IT2 in P /\ Q & ( for g being Function of I,(() | P)
for s2 being Real st g is being_homeomorphism & g . 0 = p1 & g . 1 = p2 & g . s2 = IT2 & 0 <= s2 & s2 <= 1 holds
for t being Real st 0 <= t & t < s2 holds
not g . t in Q ) implies IT1 = IT2 )

A5: P /\ Q c= Q by XBOOLE_1:17;
A6: P /\ Q c= P by XBOOLE_1:17;
assume that
A7: IT1 in P /\ Q and
A8: for g1 being Function of I,(() | P)
for s1 being Real st g1 is being_homeomorphism & g1 . 0 = p1 & g1 . 1 = p2 & g1 . s1 = IT1 & 0 <= s1 & s1 <= 1 holds
for t being Real st 0 <= t & t < s1 holds
not g1 . t in Q ; :: thesis: ( not IT2 in P /\ Q or ex g being Function of I,(() | P) ex s2 being Real st
( g is being_homeomorphism & g . 0 = p1 & g . 1 = p2 & g . s2 = IT2 & 0 <= s2 & s2 <= 1 & ex t being Real st
( 0 <= t & t < s2 & g . t in Q ) ) or IT1 = IT2 )

assume that
A9: IT2 in P /\ Q and
A10: for g2 being Function of I,(() | P)
for s2 being Real st g2 is being_homeomorphism & g2 . 0 = p1 & g2 . 1 = p2 & g2 . s2 = IT2 & 0 <= s2 & s2 <= 1 holds
for t being Real st 0 <= t & t < s2 holds
not g2 . t in Q ; :: thesis: IT1 = IT2
consider g being Function of I,(() | P) such that
A11: g is being_homeomorphism and
A12: ( g . 0 = p1 & g . 1 = p2 ) by ;
A13: rng g = [#] (() | P) by
.= P by PRE_TOPC:def 5 ;
then consider ss1 being object such that
A14: ss1 in dom g and
A15: g . ss1 = IT1 by ;
reconsider ss1 = ss1 as Real by ;
A16: 0 <= ss1 by ;
consider ss2 being object such that
A17: ss2 in dom g and
A18: g . ss2 = IT2 by ;
reconsider ss2 = ss2 as Real by ;
A19: 0 <= ss2 by ;
A20: ss1 <= 1 by ;
A21: ss2 <= 1 by ;
per cases ( ss1 < ss2 or ss1 = ss2 or ss1 > ss2 ) by XXREAL_0:1;
suppose ss1 < ss2 ; :: thesis: IT1 = IT2
hence IT1 = IT2 by A5, A7, A10, A11, A12, A15, A18, A16, A21; :: thesis: verum
end;
suppose ss1 = ss2 ; :: thesis: IT1 = IT2
hence IT1 = IT2 by ; :: thesis: verum
end;
suppose ss1 > ss2 ; :: thesis: IT1 = IT2
hence IT1 = IT2 by A5, A8, A9, A11, A12, A15, A18, A20, A19; :: thesis: verum
end;
end;